Non-parametric reconstruction of the fine structure constant with galaxy clusters - Marcelo Ferreira; Rodrigo F. L. Holanda; Javier E. Gonzalez; L. R. Colaço; Rafael C. Nunes (European Physical Journal C: Particles and Fields)
Abstract Testing possible variations in fundamental constants of nature is a crucial endeavor in observational cosmology. This paper investigates potential cosmological variations in the fine structure constant ( $$α $$ α ) through a non-parametric approach, using galaxy cluster observations as the primary cosmological probe. We employ two methodologies based on galaxy cluster gas mass fraction measurements derived from X-ray and Sunyaev–Zeldovich observations, along with luminosity distances from type Ia supernovae. We also explore how different values of the Hubble constant ( $$H_0$$ H 0 ) impact the variation of $$α $$ α across cosmic history. When using the Planck satellite’s $$H_0$$ H 0 observations, a constant $$α $$ α is ruled out at approximately the 3 $$σ $$ σ confidence level for $$z \lesssim 0.5$$ z ≲ 0.5 . Conversely, employing local estimates of $$H_0$$ H 0 restores agreement with a constant $$α $$ α .